UWB antenna with circular patch for early breast cancer detection - Aziz El Fatimi; Seddik Bri; Adil Saadi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Breast cancer is the most common cancer in women. It has the highest incidence rate and the highest mortality rate. In recent years, the incidence of breast cancer has become more and more important, it is becoming the first tumor killer for women around the world. Early diagnosis is the most important parameter for detecting cancerous tissue to prevent serious consequences. In this electronic paper, we present a new design of an ultra-wide-band circular microstrip patch antenna operating in the recommended FCC band ([3.1 GHz - 10.6 GHz]) for the detection of breast tumors. The antenna is printed on an FR4 epoxy substrate with a dielectric permittivity r = 4.4 and loss tangent tan = 0.02. The results obtained are largely satisfying and prove that the proposed antenna is a candidate for biomedical applications.